(untitled) (Palíndromo, 2022)
This paper is a reflection on Nicola Costantino’s work The True Garden is Never Green (2016), a reinterpretation of The Garden of Delights (1490-1500), by Hieronymus Bosch. The work develops in three acts, under the banner of three female mythological figures: Tethys, Aphrodite/Venus and Artemis/Diana. We will argue that representation, as used in this work, opens up a path of inquire on reality itself, and constitutes itself as an active interpretive gesture, reformulating the ways of seeing. This gesture allows Costantino to practice conjectures of herself and, by emphasizing the productive dimension of representation, builds a transforming personal experience.